CHALLENGES OF LOCAL ECONOMIC DEVELOPMENT UNIT IN SOUTH AFRICAN MUNICIPALITY - CHUNGU MAMAHLODI MASHABELA; XOLANI THUSI (Social Sciences and Education Research Review)
The purpose of the paper is to investigate the challenges encountered by the Local Economic Development (LED) unit in South African municipalities. The aim of LED is to ensure sustainable employment growth and the equal distribution of economic activities in the society. The South African government adopted LED in 1996, however, unemployment is still high. The paper seeks to propose resolutions to challenges encountered by LED in order to augment its efficacy in municipalities. The South African government is using LED to enforce the notion of quality life for all, however, there is a seemingly bottleneck when implementing LED in municipalities. Such a bottleneck hinders the optimal and maximum impact of the LED. Therefore, it is of utmost importance to identify the obstacles that pose a threat to the efficiency of LED. This will enable local municipalities to tackle these challenges effectively and strive to increase the effect of LED. The paper used qualitative and quantitative research approaches. Senior officials were interviewed while questionnaires were administered to officials within the LED department. The paper found the following challenges of the LED unit in the Polokwane Local Municipality